1994
DOI: 10.1136/bmj.308.6929.619
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive detection of malignancy by identification of unusual CD44 gene activity in exfoliated cancer cells

Abstract: Objective-To investigate non-invasive detection of cancer by testing for unusual CD44 gene activity in a clinical sample as an indicator of exfoliated tumour cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
55
0
3

Year Published

1996
1996
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 15 publications
1
55
0
3
Order By: Relevance
“…We have previously shown that elevated quantities of unusual CD44 transcripts and protein isoforms are detectable in exfoliated cells present in naturally micturated urine from bladder cancer patients (Matsumura et al, 1994). Moreover, exfoliated carcinoma cells in colon luminal washings were also shown to be detectable in about 73% of cases, when using CD44 exons 11 and 12 as detection markers .…”
Section: Discussionmentioning
confidence: 98%
“…We have previously shown that elevated quantities of unusual CD44 transcripts and protein isoforms are detectable in exfoliated cells present in naturally micturated urine from bladder cancer patients (Matsumura et al, 1994). Moreover, exfoliated carcinoma cells in colon luminal washings were also shown to be detectable in about 73% of cases, when using CD44 exons 11 and 12 as detection markers .…”
Section: Discussionmentioning
confidence: 98%
“…Qualitative and quantitative changes in expression of CD44 have been demonstrated in vitro in the vascular dissemination of melanoma (Birch et al, 1991) and lymphoma cells (Sy et al, 1991), and in the migration of rat pancreas carcinoma cells on the extracellular matrix (Günthert et al, 1991). In vivo, enhanced or upregulation of CD44 (core or variant) expression has been found to be related to tumour progression in breast (Joensuu et al, 1993), colorectal (Abbasu et al, 1993a;Tanabe et al, 1993;Wielenga et al, 1993), gastric (Heider et al, 1993a;Mayer et al, 1993), cervical (Dall et al, 1994) and bladder (Matsumura et al, 1994;Southgate et al, 1995) carcinomas, non-Hodgkin's lymphoma (Koopman et al, 1993) and brain tumours (Terpe et al, 1993). Conversely, loss of or reduction in expression of CD44v isoforms is associated with disease progression in squamous cell (Salmi et al, 1993) and endometrial carcinomas (Fujita et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Altered expression of CD44 has been observed in a large number of tumours of adult life (Matsumura and Tarin, 1992;Abbasu et al, 1993;Heider et al, 1993a;1993b;Joensuu et al, 1993;Tanabe et al, 1993;Matsumura et al, 1994;Penno et al, 1994;Southgate et al, 1995;Harwood et al, 1996;Nagabhushan et al, 1996) and in the paediatric malignancy neuroblastoma (Favrot et al, 1993;Gross et al, 1994Gross et al, , 1995Shtivelmann and Bishop, 1991). The aim of this study was to document the pattern of expression of CD44 by rhabdomyosarcomas and to determine the relationship of CD44 expression to prognosis.…”
mentioning
confidence: 99%
“…Ten of them are constitutively expressed on almost all cell types to produce a heavily glycosylated 85-90 kD isoform known as the standard form (CD44st). The remaining exons can be alternatively spliced to produce various isoforms, [5][6][7] which are called CD44 variants (CD44v). Although in humans the functions of CD44v remain unclear, they may play an important role in the growth and metastasis of several kinds of tumors.…”
mentioning
confidence: 99%